A Study on English Terms Used by the Staff of Front Office Department at the Grand Clarion Hotel Makassar - Arny Irhani Asmin (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
Register in Sociolinguistics is a form of language used for a special situation in a particular social setting, it also known as variety of language. In hotel industry, there are many kinds of English terms used by the staff both written and spoken. This study was designed to find out the English terms, the lexical meaning and the contextual meaning of the English special terms used by the staff of Front Office department in the Grand Clarion Hotel Makassar. This study employed a descriptive qualitative method. The subject of this study is the staff of Front Office department. The data were obtained through participant observation, semi-structured interview and review of the documents. The result of the study showed that the majority of terms used in Front Office department were in English. The researcher found that there were many kinds of the English terms used by the Front Office department in the Grand Clarion Hotel Makassar. In Front Office department, 85 (eighty five) English terms were found and 36 (thirty six) of them classified as the English special terms. English special terms have different meanings both lexical and contextual. These English terms in English for Specific Purposes (ESP) is called register.